The Materials Application Programming Interface (API): A simple, flexible and efficient API for materials data based on REpresentational State Transfer (REST) principles - Ong, Shyue Ping; Cholia, Shreyas; Jain, Anubhav; Brafman, Miriam; Gunter, Dan; Ceder, Gerbrand; Persson, Kristin A. (Computational materials science, 2015)
In this paper, we describe the Materials Application Programming Interface (API), a simple, flexible and efficient interface to programmatically query and interact with the Materials Project database based on the REpresentational State Transfer (REST) pattern for the web. Since its creation in Aug 2012, the Materials API has been the Materials Project’s de facto platform for data access, supporting not only the Materials Project’s many collaborative efforts but also enabling new applications and analyses. We will highlight some of these analyses enabled by the Materials API, particularly those requiring consolidation of data on a large number of materials, such as data mining of structural and property trends, and generation of phase diagrams. We will conclude with a discussion of the role of the API in building a community that is developing novel applications and analyses based on Materials Project data.